"I Says to Myself, Says I": Charles Sanders Peirce on the Components of Dialogue. Issue 3 (13th May 2016) - Crick, Nathan; Bodie, Graham D.
Abstract: Peirce famously defined the process of thinking as what a person is "'saying to himself, ' that is, is saying to that other self that is just coming into life in the flow of time." For Peirce, this meant the essence of thinking is dialogue. This essay proposes a conception of dialogue grounded in Peirce's normative ideal of inquiry that challenges contemporary thinking about dialogue yet supports the same moral and ethical aims. Using a scene from Shakespeare's Merchant of Venice that Peirce used as an exemplar of dialogue, we propose a conception that begins in doubt and passes through phases of reasoning and ethical and esthetic judgment before coming to a resolution which expands horizons of thought, emotion, and action.